2018
DOI: 10.1111/inr.12481
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceived spiritual climate of a hospital in Saudi Arabia

Abstract: Aim This study investigated the spiritual climate of a hospital in Saudi Arabia as perceived by nurses. Background A spiritually conducive environment improves patient, nurse and organizational outcomes. Despite being important, no studies have investigated this area in the Muslim‐dominated Middle Eastern countries. Introduction A snapshot on the degree of spiritual climate perception may provide insight into the aspects that may need improvement and may become basis for the creation of health and nursing poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
5
10
2
Order By: Relevance
“…Data were obtained through a cross-sectional design using two validated questionnaires and were distributed to three different hospitals with diverse nursing staff in Saudi Arabia. The findings of the study suggest promising The modest overall score of the SC corroborates earlier studies using the same tool in Saudi Arabia (Albaqawi et al, 2019;Cruz, Alquwez, et al, 2018), China (Wu et al, 2020) and Greece (Fradelos & Tzavella, 2020). However, the score in the present study was lower than that in a study conducted in the USA (Doram et al, 2017 prior studies conducted in Saudi Arabia (Albaqawi et al, 2019;Cruz, Alquwez, et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Data were obtained through a cross-sectional design using two validated questionnaires and were distributed to three different hospitals with diverse nursing staff in Saudi Arabia. The findings of the study suggest promising The modest overall score of the SC corroborates earlier studies using the same tool in Saudi Arabia (Albaqawi et al, 2019;Cruz, Alquwez, et al, 2018), China (Wu et al, 2020) and Greece (Fradelos & Tzavella, 2020). However, the score in the present study was lower than that in a study conducted in the USA (Doram et al, 2017 prior studies conducted in Saudi Arabia (Albaqawi et al, 2019;Cruz, Alquwez, et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…The percentage reporting good spiritual climate and mean score of items were lower than the findings of previous studies in America and the Middle East (Cruz, Alquwez, Albaqawi, Alharbi, & Moreno‐Lacalle, ; Doram et al, ). Item 1 “I am encouraged to express spirituality in this clinical area” received the lowest mean score, which was the same as that of Cruz (Cruz, Albaqawi, et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…For the statistical analysis of the data IBM SPSS Statistics 22 was used and as the statistical signifi-Similarly, in a cross-sectional study among 212 Koreans, Kown and Oh found that increased workplace spirituality is associated with nurses' self-efficacy and safety management activities, thus reinforcing the notion spiritual climate's positive influence on nursing care. Cruz et al (9) suggested that hospitals should revoke policies and implement interventions that foster a spiritually friendly environment and create safe places where nurses can express their spirituality regardless of their religious orientation. As a result, hospital managers can improve job satisfaction among nurses.…”
Section: Discussionmentioning
confidence: 99%